Studi Bibliometrik Jurnal Media Informatika 2018-2022 - Ronal Watrianthos; Ahmad Habin Sagala; Rahmi Syafriyeti; Yuhefizar Yuhefizar; Mesran Mesran (Universitas Budi Darma, 2023)
This study aims to conduct a bibliometric analysis of the Budidarma Informatics Media Journal (MIB) for the 2018-2022 period using the Dimensions database. The period produced 683 publications which then became the dataset in this study. The dataset was analyzed using Bibliometrix R-package Biblioshiny, and research trends were mapped using VOSviewer visualization. The analysis results show that the collaboration index of MIB journals has a moderate value and tends to be low, although the annual growth rate of 79.08% looks very significant. The number of citations over five years only amounted to 157, so the average citation per article was 0.22. The average FCR is 0.16, which indicates a citation that is well below average. The results of testing Lotka's postulates for author productivity in this period showed a significant difference between the analysis results and the theory in Lotka's postulates. As for trends, research related to